Qualification of Adult Educators in Europe: Insights From the Portuguese Case - Catarina Paulos (European Research Network Vocational Education and Training (VETNET), 2015)
This article explores the role of the European Union in defining an adult education policy and the way European countries appropriate those guidelines and implement them in their realities. These policies have been widening and diversifying adult education, creating the necessity of qualifying educational professionals. With the implementation of some adult education political measures, new educational practices were developed and new professional activities were born. This investigation is about the qualification of adult educators working in the processes of recognition of prior learning.